Environmental heterogeneity influences life-form richness and species composition but not species richness of aquatic macrophytes in tropical coastal rivers - Nunes, Laís Samira Correia [UNESP]; Umetsu, Cristiane Akemi [UNESP]; Camargo, Antonio Fernando Monteiro [UNESP] (Wiley, 2020)
The coastal rivers of the São Paulo State in SE Brazil have different lengths and seawater influence. We evaluated whether: (1) environmental heterogeneity (EH) is associated with the species and life-form richness of aquatic macrophytes; and (2) EH and geographical distance influence species composition in these coastal rivers. We recorded the macrophyte species and life form occurrence and collected explanatory variables characterising the water, sediment, and river channel at 100 sampling sites over 8 rivers. We applied a principal component analysis to the explanatory variables and calculated the rivers' EH using the range of principal component 1 scores. We also determined the position of each river mouth along the coastline to measure the distance between the rivers. We used quasi-Poisson generalised linear models to evaluate the effects of EH on richness of species and life forms. To determine the effect of EH and geographical distance (Euclidean distance matrices) on the variation in species composition (Jaccard dissimilarity matrix) among the rivers, we applied multiple regressions on distance matrices. The most heterogeneous river had heterogeneity score about five times greater than the least heterogeneous river. Sediment salinity, river width, total phosphorus concentration of water and distance from river mouth were the most important variables contributing to the rivers' EH. We found that EH did not explain variation in species richness; however, it had a significant positive relationship with life-form richness. The effect of EH was greater than that of the geographical distance on the variation in species composition among the rivers. The pairs of rivers with the most similar EH were the most similar in species composition, but not all of them were geographically close. We conclude that EH influences life-form richness but does not influence species richness of aquatic macrophytes in the coastal rivers we studied; however, EH does influence species composition regardless of geographical distance among rivers.
Keywords: aquatic plants; coastal plain; estuaries; macrophyte composition; river heterogeneity